Previdência pública brasileira em uma perspectiva internacional: Custeio, benefícios e gastos - Milko Matijascic (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– Financing and eligibility rules in Brazilian social security, when compared to other countries are inserted on a national debate that presents clear limitations when the focus is turns to social rights. According to the international experience, there are important differences among developed countries and the other ones. Developed countries present a situation based on high contribution rates to social security and such a scenario is not similar in Latin American or BRICS' countries. To increase coverage there is a need to consolidate universal rights and social assistance initiatives based on cash transfers. Expenditures with old age benefits are growing since the insured are ageing and resist to radical reforms. Nevertheless, survivor and incapacity benefits are presenting decreasing costs. The main difference among developed countries and the other ones are centered in the growing importance focused on social benefits for families, since the first group seems to reduce spending and the other one is raising it.
Keywords: I30; 330; social security; international comparison; social cost